Multiple view geometry in computer vision - Hartley, Richard; Zisserman, Andrew
A basic problem in computer vision is to understand the structure of a real world scene given several images of it. Techniques for solving this problem are taken from projective geometry and photogrammetry. Here, the authors cover geometric principles and algebraic representation in terms of projection matrices of the camera, the fundamental matrix and the trifocal tensor. The theory and methods of calculation of these entities are discussed with real examples, as is its use in the reconstruction of scenes from multiple images. The new edition features an expanded introduction covering the key ideas in the book (which itself has been updated with additional examples and appendices) and significant new results that have appeared since the first edition. Comprehensive support material is provided, so readers familiar with linear algebra and basic numerical methods can understand the algorithms and projective geometry estimation presented, and implement algorithms directly from the book.